Three-dimensional viscous flow and heat transfer over a permeable shrinking sheet - Hafidzuddin, Mohd Ezad Hafidz; Nazar, Roslinda; Md. Arifin, Norihan; Pop, Ioan (Elsevier, 2014)
This paper presents a numerical analysis of a steady three-dimensional fluid flow and heat transfer towards a permeable shrinking sheet. The governing nonlinear partial differential equations are transformed into a system of ordinary differential equations by a similarity transformation, which are then solved numerically by a shooting method. The effects of the governing parameters on the skin friction and heat transfer from the surface of the shrinking surface are illustrated graphically. It is found that dual solutions exist for the shrinking case. A comparison with known results from the open literature has been done and it is shown to be in excellent agreement.